2018
DOI: 10.1101/270108
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Kaposi’s Sarcoma-Associated Herpesvirus Infection Mechanism is Independent of Integrins α3β1, αVβ3, and αVβ5

Abstract: Host receptor usage by KSHV has been best studied using endothelial and fibroblast cells in 24 tissue culture. In these models, KSHV adheres to the cell though heparan sulfate (HS) binding, then 25 interacts with a complex of EphA2, xct, and integrins α3β1, αVβ3, αVβ5 to catalyze viral entry. We 26 dissected this receptor complex at the genetic level with CRISPR-Cas9 to precisely determine receptor 27 usage in two epithelial cell lines. Surprisingly, we discovered an infection mechanism that requires HS 28 and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 74 publications
1
5
0
Order By: Relevance
“…EphA4 is widely expressed in different tissues and cell types (3). Using RNA-seq analysis we 244 found that EphA4 is expressed in B cells, fibroblasts, epithelial cells, and endothelial cells ( an integrin-independent route of KSHV infection and also suggests that multiple Eph receptors 253 besides EphA2 can promote and regulate infection, consistent with our findings (11). 254…”
supporting
confidence: 81%
“…EphA4 is widely expressed in different tissues and cell types (3). Using RNA-seq analysis we 244 found that EphA4 is expressed in B cells, fibroblasts, epithelial cells, and endothelial cells ( an integrin-independent route of KSHV infection and also suggests that multiple Eph receptors 253 besides EphA2 can promote and regulate infection, consistent with our findings (11). 254…”
supporting
confidence: 81%
“…Although it was shown that host cell entry, assembly and release of various viruses are mediated by the Tspans in a dependent or independent manner (through their partners such as integrins), there is currently no evidence, other than the FimH/Tspan21 complex, that bacteria interact with Tspans directly. The major function of Tspans during bacterial infection may rely on connecting bacterial ligands to additional surface proteins belonging to TEMs platforms, such as integrins (Rajan et al, 2018; Storm et al, 2017; TerBush, Hafkamp, Lee, & Coscoy, 2018). Thus, further work is required to unravel the contribution of individual Tspans or their cognate partners in the different processes leading to bacterial colonisation of the host.…”
Section: Discussionmentioning
confidence: 99%
“…Because EphA2 recognizes b-glucans on pathogenic fungi other than C. albicans, such as Aspergillus fumigatus and Rhizopus oryzae (Swidergall et al, 2018), it is probable that it enhances the neutrophil response to these organisms too. Moreover, EphA2 has been found to recognize Plasmodium, Chlamydia trachomatis, and several viruses (Chen et al, 2018;Kaushansky et al, 2015;Lupberger et al, 2011;Subbarayal et al, 2015;TerBush et al, 2018;Zhang et al, 2018). However, the studies with these organisms were performed using normally nonphagocytic host cells, such as hepatocytes or epithelial cells.…”
Section: Discussionmentioning
confidence: 99%